A Study Of Versions Of The Epic “Alpamish” (Eurasian Journal of Humanities and Social Sciences, 2025)
This article examines the Kazakh and Karakalpak versions of the most famous Uzbek folklore epic “Alpamish”, and discusses their similarities and differences. Several hypotheses regarding the names of the regions where the epic takes place are analyzed.